Forecasting of Murine Embryo Osmotic Behaviour at Main Stages of Cryopreservation - Pishko, O. V.; Smolyaninova, E. I.; Kovalenko, I. F.; Kovalenko, S. E.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2004)
There were determined the transport characteristics for zygotes, 2- and 8-cell murine embryos. Basing on the obtained permeability coefficients and corresponding geometric cell parameters the modelling of cell osmotic behaviour at the stages of cryoprotectant adding to embryos, as well as at the stages of embryo freezing with different cooling rates and cryoprotectant removal out of cells, was carried-out.